Pengaruh Pemahaman Akuntansi, Literasi Keuangan, Modal Usaha, Kreativitas dan Pemanfaatan Media Sosial Terhadap Keberlanjutan UMKM Di Kecamatan Negara - Ni Komang Trisnadewi; Nyoman Ayu Wulan Trisna Dewi (Universitas Pendidikan Ganesha, 2023)
Abstract The purpose of this study was to determine the effect of understanding accounting, financial literacy, venture capital, creativity, and the use of social media on the sustainability of MSMEs in Negara District. This study uses a quantitative research design using a data collection instrument in the form of a questionnaire. The population used in this study is formal MSME actors in the Negara District. Determination of the sample in this study using purposive sampling method which will calculate the minimum number of samples using the Slovin formula which results in a calculation of 312 samples from a total population of 1,425 MSMEs. Data analysis in this study used descriptive analysis, variable measurement, data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing using SPSS version 25. The results of this study obtained the results that accounting understanding, financial literacy, venture capital, creativity, and the use of social media has a positive and significant impact on the sustainability of MSMEs in Negara District. Keywords: Accounting Understanding, Financial Literacy, Business Capital, Creativity, Utilization of Social Media, MSME Sustainability.